Earthquake Triggering: Verification of Insights Obtained by Intuitive Consensus - Kautz, William H. (Journal of Scientific Exploration, 2012)
<!--[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman";} --> <!--[endif] -->Up until 1980 seismology was focused entirely upon data collection, the long-term study of tectonic processes, and limited surface-level measurements. Formal research on earthquakes was almost at a standstill despite the urgent need to discover reliable and measurable precursors in support of a system for short-term prediction. In the period 1975–1978 the author chose to interview eight intuitive experts who had proven their abilities in domains other than seismology. He asked them identical questions about the physical process involved in earthquake-triggering and associated precursors, and then compiled their consistent responses into a consensus. The accounts agreed well with one another and offered a number of insightful and possibly new directions for seismological research. Re-examination of these intuitive findings thirty years later, in the light of the many subsequent discoveries reported in mainstream geophysics journals, revealed that the expert intuitives had provided novel, significant, and strikingly correct information on earthquake-triggering and related precursors. This exemplary result suggests that skillfully applied intuitive inquiry could play a significant role in future seismological and geophysical studies, as well as in scientific research generally. Keywords: earthquakes—intuition—intuitive consensus—expert intuitives—earth-quake triggering—seismology—geophysics—prediction—verification—nuclear activity—precursors—tectonic plates —atmospheric electricity—electromagnetism—faults—earthquake lights—solar wind—thermal anomalies—solar activity—magnetosphere—ground gases—earth tides—planets—atmosphere—weather changes—animal behavior—human-caused earthquakes